Cirtisim of Naat and “Naat Rang” - Sabir Hussain Jafri; Dr. Rabia Sarfaraz (Zaban-o-Adab, 2021)
The article introduces Book Series “Naat Rang” in general and its efforts to promote Criticism on the texts and expressions of devotional poetry, in conforming to literary norms, in particular. 29 issues of “Naat Rang” have so far been published since its first appearance in April 1995. A brief history of idea of bringing genre of Naat in literary discourse has also been presented herein. Involvement of famous literary figures in the critical discussion in respect of Naat, seems to be miraculous achievement of “Naat Rang”. “Naat Rang” has achieved international fame till now and has gained heed of world fame writers to join the literary circle of this valuable book series.